(untitled) (Cambridge, UK, 2002)
This edition presents Medea, the most famous play of the Athenian tragedian Euripides, in ancient Greek, with commentary designed for university Greek classes, from second-year Greek upward. It helps students experience a classic drama as they work through the process of careful translation and gives them an appreciation of the work's artistry and its relation to its culture and performance tradition.
Keywords: Medea (Greek mythology)